Re-appraising the evidence for the source, regulation and function of p53-family isoforms - López, Ignacio; Valdivia, Irene Larghero; Vojtesek, Borivoj; Fåhraeus, Robin; Coates, Philip J (Nucleic acids research, 2024)
The p53 family of proteins evolved from a common ancestor into three separate genes encoding proteins that act as transcription factors with distinct cellular roles. Isoforms of each member that lack specific regions or domains are suggested to result from alternative transcription start sites, alternative splicing or alternative translation initiation, and have the potential to exponentially increase the functional repertoire of each gene. However, evidence supporting the presence of individual protein variants at functional levels is often limited and is inferred by mRNA detection using highly sensitive amplification techniques. We provide a critical appraisal of the current evidence for the origins, expression, functions and regulation of p53-family isoforms. We conclude that despite the wealth of publications, several putative isoforms remain poorly established. Future research with improved technical approaches and the generation of isoform-specific protein detection reagents is required to establish the physiological relevance of p53-family isoforms in health and disease. In addition, our analyses suggest that p53-family variants evolved partly through convergent rather than divergent evolution from the ancestral gene.
Keywords: Evolution, Molecular; molekulární evoluce; nádorový supresorový protein p53; alternativní sestřih; protein - isoformy; Protein Isoforms; RNA, Messenger; Transcription Initiation Site; Animals; Humans; Gene Expression Regulation; počátek transkripce; messenger RNA; lidé; zvířata; regulace genové exprese; Alternative Splicing; Tumor Suppressor Protein p53